Distributed Diode Single-Balanced Mixer Using Defected and Protruded Structures for Doppler Radar Applications - Ebrahimian, H.; Ojaroudi, M.; Ojaroudi, N.; Ghadimi, N. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a single-balanced diode mixer using defected and protruded structures for wireless application is presented. The operating frequency is selected for WLAN applications. The RF frequency is 2.412-2.484 GHz and the Local Oscillator (LO) is 2.132-2.204 GHz for 269 MHz Intermediate Frequency (IF) output signal. A Branch-Line Coupler is designed for the singlebalanced of mixer. Four protruded T-shaped strip are used to obtain good convention gain and suppress unwanted harmonics. Also by using Defected Ground Structure (DGS) with folded Tshaped arms in the filter, a harmonic rejection property is generated. The measured performances of fabricated circuit conventionalize to the simulated results and LO to RF isolation is lower than -20 dB, LO to IF isolation is lower than -28 dB and Radio Frequency (RF) to IF is lower than -37 dB.